Offshore pipeline decommissioning: Scale and context. Issue 1 (April 2018) - Rouse, Sally; Hayes, Peter; Davies, Ian M.; Wilding, Thomas A.
Abstract: The spatial extent of human activities must be understood for consistent and proportionate regulation, and effective marine planning. Redundant offshore pipelines can be removed or left in situ, but data on the footprint of these options are not readily available. The extents of three North Sea in situ decommissioning scenarios are presented. Leaving pipelines in situ would occupy <0.01% (12.3 km 2 ) of UK waters, and this was similar to, or smaller than, other regulated activities ( e.g. aggregate extraction). Adding armouring to large pipelines occupied up to 95 km 2, while creating fisheries exclusion zones occupied up to 1119 km 2 . Removal of pipelines >30″ would be required to regain 50% or more of the seabed currently occupied. At present, the technology to remove pipelines >16″ safely and cost-efficiently is untested for large-scale decommissioning projects. The summaries presented inform the debate over the significance of decommissioning, and the regional consequences of different options. Highlights: The spatial extents of 3 in situ pipeline decommissioning scenarios were calculated. Existing pipelines have the third smallest footprint of all UK human activities. Leaving pipelines in situ occupied <0.01% of UK waters. Exclusion zones occupied more area than rock dump as fisheries risk mitigation. Technology advances are needed to regain the use of most pipeline-occupied areas.